Research on Strategy of distributed energy storage aggregators participating in peak load regulation auxiliary service. Issue 1 (March 2021) - Dunnan, Liu; Yuan, Gao; Tingting, Zhang; Jiahao, Liang
Abstract: In view of the peak shaving problem caused by high proportion of renewable energy connected to the grid, this paper proposes a trading mode in which the distributed energy storage aggregator participates in the peak shaving auxiliary service market, analyzes the operation mode of DSAP participating in peak shaving auxiliary service, and puts forward the optimization model and scheduling strategy of DSAP participating in peak shaving. The feasibility and effectiveness of DSAP participating in peak shaving auxiliary service are verified by numerical simulation.